IMPLEMENTASI ALGORITMA RABIN KARP DAN OPTIMASI DENGAN ALGORITMA STEMMER SASTRAWI DALAM DETEKSI PLAGIAT PADA JURNAL SKRIPSI MAHASISWA - Herman (Majalah Ilmiah METHODA, 2024)
The problem of plagiarism is a serious problem in tertiary institutions, given the high number of plagiarism acts that do not uphold the principle of honesty. Problems related to plagiarism in the academic field have been widely discussed in previous studies. However, previous studies that were conducted only focused on checking thesis similarities, but had not implemented the stemming algorithm in processing the data used in the research. Therefore, in this study a plagiarism detection system will be developed in thesis journals by implementing the Rabin Karp algorithm and optimization with the Literary Stemmer algorithm so that it is expected to increase the accuracy of the results of plagiarism detection. Based on the results of tests carried out through a combination of the Rabin Karp algorithm and optimization with Stemmer Literature in detecting plagiarism of student thesis journals, an accuracy rate of 80% was obtained in detecting similarities in student thesis journals in this study and the average speed of execution time was 25.6934 seconds.